Derry, Bloody Sunday, and the “Great Sea-Change” - Robinson, Joseph S. (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2023)
In 2010, 13 of the 14 victims of Bloody Sunday were publicly exonerated by the Report of the Bloody Sunday Inquiry after the lengthy struggle of the Bloody Sunday Justice Campaign (BSJC). By 2011 however, the BSJC publicly fractured over the impact of the Report and whether to continue the annual Bloody Sunday March. This article argues the split in the BSJC is a proxy for a broader struggle between divergent “spatial stories” (de Certeau 1984) of the city of Derry itself. Will Derry be narrated as a city transcending its difficult past or will the original struggle remain perpetually present?
Keywords: Derry; krvava nedelja; nasprotujoče si razlage; Severna Irska